COOPERATION IN THE FIGHT AGAINST ECONOMIC AND FINANCIAL CRIME IN THE EUROPEAN UNION - Bugarski, Tatjana; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The idea of the European Public Prosecutor's Office as a supranational body has been part of the academic and political discussion on the development of the common area of criminal justice of the European Union since the 1990s. The European Commission presented a proposal for the establishment of such a body in 2013, which was followed by negotiations between the member states and the EU institutions, in order to find a balance between the preservation of the sovereignty of the member states in the domain of criminal law and the effective protection of supranational value, i.e. the protection of the financial interests of the Union. The European Public Prosecutor's Office was established in 2017, and represents a form of enhanced cooperation between member states that have decided to participate in the work of the European Public Prosecutor's Office. After the organizational, normative, personnel and technical prerequisites have been met, the European Public Prosecutor's Office started its work on June 1, 2021. In this paper, the authors analyze the process of fulfilling the previous conditions, the beginning of work and the activities of the European Public Prosecutor's Office so far.